A predictor-corrector interior-point algorithmfor monotone variational inequality problems - 梁昔明 钱积新 (Journal of Zhejiang University. Science, 2002)
Mehrotra' s recent suggestion of a predictor-eorrector variant of primal-dual interior-point method for linear programming is currently the interior-point method of choice for linear programming.In this work the authors give a predictor-corrector interior-point algorithm for monotone variational inequality problems. The algorithm was proved to be equivalent to a level-1 perturbed composite Newton method. Computations in the algorithm do not require the initial iteration to be feasible. Numerical results of experiments are presented.